Disrupted Brain Functional Network Architecture in Chronic Tinnitus Patients - Chen, Yu-Chen; Feng, Yuan; Xu, Jin-Jing; Mao, Cun-Nan; Xia, Wenqing; Ren, Jun; Yin, Xindao (Frontiers in Aging Neuroscience, 2016)
Purpose: Resting-state functional magnetic resonance imaging (fMRI) studies have demonstrated the disruptions of multiple brain networks in tinnitus patients. Nonetheless, several studies found no differences in network processing between tinnitus patients and healthy controls. Its neural bases are poorly understood. To identify aberrant brain network architecture involved in chronic tinnitus, we compared the resting-state fMRI patterns of tinnitus patients and healthy controls. Materials and Methods: Chronic tinnitus patients (n=24) with normal hearing thresholds and age-, sex-, education- and hearing threshold-matched healthy controls (n=22) participated in the current study and underwent the resting-state fMRI scanning. We used degree centrality to investigate functional connectivity strength of the whole-brain network and Granger causality to analyze effective connectivity in order to explore directional aspects involved in tinnitus. Results: Compared to healthy controls, we found significantly increased network centrality in bilateral superior frontal gyrus (SFG). Unidirectionally, the left SFG revealed increased effective connectivity to the left middle orbitofrontal cortex (OFC), left posterior lobe of cerebellum, left postcentral gyrus, and right middle occipital gyrus while the right SFG exhibited enhanced effective connectivity to the right supplementary motor area (SMA). In addition, the effective connectivity from the bilateral SFG to the OFC and SMA showed positive correlations with tinnitus distress. Conclusions: Resting-state fMRI provides a new and novel method for identifying aberrant brain network architecture. Chronic tinnitus patients have disrupted functional connectivity strength and causal connectivity mostly in non-auditory regions, especially the prefrontal cortex. The current findings will provide a new perspective for understanding the neuropathophysiological mechanisms in chronic tinnitus.